Toward greener construction: Advancing self-compacting lightweight mortars with sustainable binders and multiscale performance evaluation - Ulucan, Muhammed; Cebeci, Ibrahim; Yetkin, Musa; Alyamac, Kursat Esat (Elsevier, 2026)
This study focuses on exploring the engineering and environmental properties of self-compacting lightweight mortars designed to reduce the environmental outputs of waste materials obtained from buildings demolished by destructive earthquakes, incorporate these waste materials, and minimize carbon emissions. Ten different self-compacting lightweight mortars were prepared using pumice and recycled materials as aggregates, metakaolin and ground granulated blast furnace slag as combination supplementary cementitious materials (SCM). MK15 indicated a 13.9-11.9 % improvement in final age compressive and flexural strengths (180 days). Approximately 40-65 % decrease in flexural and compressive strengths at 600 and 900 degrees C. In sulphate resistance tests, the lowest decrease in compressive and flexural strength (5.3-5.7 %) was observed in GGBFS10. SCM was found to deliver striking results across five impact categories, identifying the critical importance of cement for greener construction technologies and the effectiveness of design. To this end, this research provides a sustainable approach to reduce earthquake-related waste stock, environmental outputs, and cement consumption by incorporating waste materials into self-compacting concrete and mortar technology, which is widely used in new buildings in Turkey, a country that has been exposed to devastating earthquakes in recent years.
Keywords: Green construction; Self-compacting lightweight mortar; Recycled aggregate; Life cycle assessment